A System for Adaptive Suppressing the Ignition of Materials and Substances; Journal of Engineering Physics and Thermophysics; Vol. 97, iss. 7 - Glotov M. I. Maksim Ivanovich (2024, 2024)
By using a model room, the conditions are reproduced for the functioning of the system of early identification of ignition originated due to the statistically most typical causes and its effective suppression are represented due to the timely and reliable information on the type of fire source, its size and position, and on pyrolyzing material and its mass. The response characteristics of different types of fire detectors are recorded. Specialized software has been developed that allows accumulating statistics on the response of various types of sensors in a model room, analyzing statistical data and issuing recommendations for the fire safety system operator. Statistical data are used by a neural network to determine the type of combustible material, its mass, material heating mechanism, and the volume of extinguishing agent necessary and sufficient to localize and suppress combustion of the material. The proposed adaptive approach to fire extinguishing allows one to significantly reduce the amount of water required to suppress the fire source and the time of its extinguishing